2011
DOI: 10.7763/ijiet.2011.v1.62
|View full text |Cite
|
Sign up to set email alerts
|

Educational Performance: The Role of Background Variables

Abstract: In the present time the accounting profession has faced two main challenges. The first challenge is the change and spread of the accounting role which has caused increasing demand for the skilled and professional graduates and the second one is related to existence of a gap between the current skills and the desired skills among the graduates of accounting field. This problem can be assigned to the lack of attention to effective factors of learning and training. Some believe that the educational program of acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…There was a contradiction in the attribution of the teachers to lack of prior knowledge in accounting as the primary cause of students' failure. Although various studies (Papageorgiou, 2017;Al-Mutairi, 2011;Alanzi, 2015;Marinaccio, 2017;Nayebzadeh, Aldin, & Heirany, 2011;Arquero, Byrne, Flood & Gonzales, 2009) conducted around the world proved the importance of prior knowledge, the current study found it not significant to either success or failure of the student in accounting subject. There was no strong reference for failure to teacher-factors such as qualifications and inappropriate teaching methodology.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…There was a contradiction in the attribution of the teachers to lack of prior knowledge in accounting as the primary cause of students' failure. Although various studies (Papageorgiou, 2017;Al-Mutairi, 2011;Alanzi, 2015;Marinaccio, 2017;Nayebzadeh, Aldin, & Heirany, 2011;Arquero, Byrne, Flood & Gonzales, 2009) conducted around the world proved the importance of prior knowledge, the current study found it not significant to either success or failure of the student in accounting subject. There was no strong reference for failure to teacher-factors such as qualifications and inappropriate teaching methodology.…”
Section: Discussioncontrasting
confidence: 73%
“…Taking the different studies that depicted on the importance of the previous knowledge in the study of accounting (Papageorgiou, 2017;Al-Mutairi, 2011;Alanzi, 2015;Marinaccio, 2017;Nayebzadeh, Aldin, & Heirany, 2011;Arquero, Byrne, Flood & Gonzales, 2009), the results of the current study show that students have sufficient background of the subject. Thus, it may not be a factor for failure.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In most of the business programs, accounting is regarded as highly challenging than any other business modules due to its global phenomenon of high failure rate (Alanzi, 2015;Borges, Santos, Abbas, Marques & Tonin, 2014;Fakoya, 2014). The most common identified student-related factors associated with academic performance include students' individual characteristics (Bean, Bush, McKenry & Wilson, 2003), personal responsibility of the learners (Gracia & Jenkins, 2002), commitment and procrastination (Borges, Santos, Abbas, Marques & Tonin, 2014), attendance (Duve, 2016;Alanzi, 2015;Jameel & Hamdan, 2015), prior knowledge (Nayebzadeh, Aldin, & Heirany, 2011;Al-Mutairi, 2011;De Villiers & Farrington, 2017), motivation and determination (Xiang & Hinchliffe, 2019) and learning techniques (Ozpeynirci, Yucenur, Duman & Apak, 2013). Moreover, studies conducted in English as Second Language (ESL) countries, academic performance is mostly associated with knowledge of English (Sebrina, Serly & Taqwa, 2018;De Villiers & Farrington, 2017) and surprisingly, nationality (Al-Mutairi, 2011).…”
Section: Introductionmentioning
confidence: 99%